PENGARUH PENERAPAN TEKNIK THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 27 PADANG - Fitri, Yulisa; Zulfaneti, Zulfaneti; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACT This research are motivated by the students comprehension of mathematical concept is still low and students are less willing to share in group. The purpose of this research is to determine whether students comprehension of mathematical concept by implementing the Thinking loud Pair Problem Solving (TAPPS) technique is better than students comprehension of mathematical concept by implementing conventional learning in class VIII SMPN 27 Padang. this was an experimental research which used pre experimental design: static groupcomparison. The sampling was done by purposive sampling. The  sampling in this research are class VIII.5 and VIII.6. Instrument used is test comprehension of mathematical concept in the form of essay. Based on the result of item analysis, it was revealed that final test item was reliable with r11 = 0,80 and rtable  = 0,388. Hypothesis test used t-test one way with MINITAB software. Based on the math final test result from both of the sample class obtained that tvalue = 2,07 while ttable = 1,65, because tvalue  ttable, then hypothesis was received. It can be conclude that Students comprehension of mathematical concept by implementing Thinking Aloud Pair Problem Solving (TAAPS) is better than students comprehension of mathematical concept.